In Vitro Transformation of the Retina in 3d Model - Hamzayeva Nargiza Rajabboyevna; Khayrullayeva Lobar Mansur kizi (Genius Publishing Group, 2022)
Many models have been developed to illuminate the human eye and its pathology, formation, and morphology, as well as its function. Micro physiological in vitro models or the creation of microchip internal organs of the eye serve as a new technology to solve a number of problems of the visual capacity. In particular, the inability to obtain and use in vitro 3D bio printing , the collection of 3D biological structures, and the ability of these structures to direct tissue construction play an important role in ophthalmology and tissue engineering
Keywords: Microchip internal organs; in vitro models; 3D bio printing